Antidumping and Product Quality - Mauro Caselli; Jiuli Huang; Chiara Tomasi; Min Zhu (Centre for Inclusive Trade Policy (CITP), University of Sussex Business School, 2023)
We examine the export behaviour of Chinese firms, in particular firms' decision on product quality, in the face of product- and market-specific tariff shocks that arise when importers impose anti-dumping duties. Exploiting the time-varying trade policy changes from the Global Antidumping Database and transaction-level Chinese customs data between 2000 and 2015, we find that Chinese firms hit by anti-dumping duties tend to decrease not only the export flows but also the quality of the targeted products, while no significant effect is found for prices. We show that the results are robust to several sensitivity checks. The estimated impact of quality downgrading continues even after the measure is revoked and it is more pronounced for firms exporting to developing countries. Further results allow us to better understand the underlying mechanism. Specifically, firms exposed to anti-dumping duties respond by importing input varieties with lower prices, which contributes to reduce the quality of their products. Back-of-the-envelope calculations show that countries imposing anti-dumping measures experience a 5.4% loss in consumer surplus for the targeted products.
Keywords: F13; F14; D22; 330; anti-dumping; China; trade; quality; imported inputs